Monitoring of moorland birds in Northeastern Iceland - Snæþórsson, Aðalsteinn Örn; Snæþórsson, Aðalsteinn Örn (Polar Data Catalogue, 2015)
The breeding numbers and density of different species is estimated annually from point counts. Abiotic factors are monitored at fixed weather stations in the area by the Icelandic Meteorological Office.